Color-space analysis for facial feature detection - Demirel, Hasan (Institute of Electrical and Electronics Engineers Inc., 2002)
Facial feature detection is an important preprocessing step used in facial image processing. Most of the image-based facial feature detection techniques use only the luminance information ignoring the color information of the images. We introduce a method of adding color-space information to the principal component analysis (PCA) based eigen features technique. The experimental results show that the color information helps to improve the detection performance of the detectors when compared with the detectors using only the luminance information. © 2002 Croatian Soc. Electronics in Marine-ELMAR.
4th EURASIP - IEEE Region 8 International Symposium on Video / Image Processing and Multimedia Communications, VIPromCom 2002 -- 2002-06-16 through 2002-06-19 -- Zadar -- 116191
Keywords: color eigenfeatures; Facial feature detection